Clinical spectrum of Pediatric HIV across A.R.T. centers in Chhattisgarh - Sharja Phuljhele; Shashikant Dewangan; Shrikant Sanadhya (International Journal of Medical Research and Review, 2017)
Introduction: Pediatric HIV is a major world health problem, which is progressing at an alarming rate. Few studies have been done about variable clinical manifestation of pediatric HIV infection in children. This study intends to know the clinical profile of HIV infection in children of Chhattisgarh, evaluate the seroconversion rates of babies born to HIV seropositive women, possible maternal, obstetrical, and feeding factors influencing them, patient’s adherence to ART and opportunistic infections in affected children.Methods: All pediatric HIV cases from 1½ year to 14 year registered in A.R.T. centres of Chhattisgarh. Data were analysed using SPSS system version 21.Result: A total of 414 children were evaluated from different A.R.T. centres in Chhattisgarh for final analysis. Male to female ratio is 1.38:1. Most common mode of transmission is from mother to child. Tuberculosis, Recurrent and Persistent Diarrhoea, Recurrent Pneumonia and Oral Candidiasis are common infection in most of the children.Conclusion: Average age of diagnosis of pediatric HIV is around 7.5 ± 2.1years. Majority of children are diagnosed in stage 3. Adherence therapy to A.R.T. is good. Vertical transmission is most common mode of transmission.